Qualitative analysis of clinician experience in utilising the BuRN Tool (Burns Risk assessment for Neglect or abuse Tool) in clinical practice. Issue 7 (November 2018) - Mullen, Stephen; Quinn-Scoggins, Harriet D.; Nuttall, Diane; Kemp, Alison M.
Highlights: Qualitative analysis of clinician experience in utilising the BuRN Tool. BuRN-Tool an acceptable aid in identifying child maltreatment in patients with burns. The greatest perceived benefit is for junior staff and those that do not regularly work in paediatrics. Abstract: Introduction: The BuRN-Tool (Burns Risk assessment for Neglect or abuse Tool) is a clinical prediction tool (CPT) aiding the identification of child maltreatment in children with burn injuries. The tool has been derived from systematic reviews and epidemiological studies, validated and is under-going an implementation evaluation. Clinician opinion on the use of this CPT is a key part of its evaluation. Objectives: To explore the experience of emergency clinicians use of the BuRN-Tool in an emergency department (ED). Methods: Three focus groups were conducted over a six-week period by the research team in the ED in the University Hospital of Wales; 25 emergency clinicians attended. A semi-structured approach was taken with pre-determined open-ended questions asked followed by a series of case vignettes to which the CPT was applied. The focus groups were recorded and transcribed verbatim. Thematic analysis was conducted for identification of pre-set and emergent themes. All data were double-coded. Results: All participants said that it was acceptable to use the BuRN-Tool to aid in the decision-making process surrounding child maltreatment. All participants said that the BuRN-Tool was helpful and straight forward to use. All participants said that the tool was clinically beneficial, particularly for junior staff and those who do not always work in a paediatric environment. The clinical vignettes identified subjectivity in interpretation questions around adequate supervision, previous social care involvement and full thickness burns. This resulted in some variation in scoring. Conclusions: This study confirms that the BuRN-Tool is acceptable in an ED setting. The focus groups demonstrated a homogenous and positive attitude regarding the layout, benefits and use of the BuRN-Tool. The subjective interpretation of some variables accounts for the non-uniformity in the scores generated. Clarification of questions will be made.